2014
DOI: 10.18869/acadpub.rmm.2.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Association between Epstein - Barr Virus (EBV) and Breast Cancer

Abstract: Background: Breast cancer is the most common malignancy in females worldwide. Several etiological factors including environmental factors have been recognized for breast cancer. Epstein Barr virus as a viral etiological factor has been proposed. So far, several studies have investigated the relationship between development of breast cancer and Epstein Barr virus, but few have been done in Iran. The aim of this study was to determine whether there was an association between EBV infection and female breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…For EBV, the screening of the viral genome did not show any correlation with the case and control groups (P = 0.164) ( Table 3). The rate of EBV infection in breast cancer patients was not unexpected, as the virus has been detected in many studies to be absent or be at a low rate at this site (45)(46)(47). However, we did not observe any significant association between breast cancer and EBV presence.…”
Section: Discussioncontrasting
confidence: 49%
“…For EBV, the screening of the viral genome did not show any correlation with the case and control groups (P = 0.164) ( Table 3). The rate of EBV infection in breast cancer patients was not unexpected, as the virus has been detected in many studies to be absent or be at a low rate at this site (45)(46)(47). However, we did not observe any significant association between breast cancer and EBV presence.…”
Section: Discussioncontrasting
confidence: 49%
“…The low frequency of 7.3% EBV DNA have been reported among the breast cancer in Iran (Torabizadeh et al, 2014). While high frequency of 55.5% of EBV DNA detection in women with breast cancer have been reported in Sudan (Yahia et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Eghbali et al [16] in Tehran, Iran, reported EBV infection in 16.6% of carcinoma and 4.1% of fibroadenoma samples, but this infection rate was statistically insignificant. A low frequency (7.3%) of EBV DNA have also been reported among the breast cancer in another study in Iran [17] .…”
Section: Discussionmentioning
confidence: 65%